2012
DOI: 10.1182/blood-2012-06-438911
|View full text |Cite
|
Sign up to set email alerts
|

B cells from patients with chronic GVHD are activated and primed for survival via BAFF-mediated pathways

Abstract: Recent data reveal an important role for B cells in the pathogenesis of chronic GVHD (cGVHD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
119
1
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(142 citation statements)
references
References 46 publications
18
119
1
4
Order By: Relevance
“…On the other hand, and in contrast to our expectation, we observed lower sjKRECs and cjKRECs from 3 months to 2 years in patients with chronic GVHD (Supplementary Figure 5). This observation does not support the data of Allen et al, 26 which revealed increased numbers of B cells and expression of BAFF (B-cell-activating factor belonging to the TNF family) in patients with chronic GVHD. This discrepancy may be because the patients with chronic GVHD were on more active immunosuppressants compared with those without chronic GVHD.…”
Section: Discussioncontrasting
confidence: 57%
“…On the other hand, and in contrast to our expectation, we observed lower sjKRECs and cjKRECs from 3 months to 2 years in patients with chronic GVHD (Supplementary Figure 5). This observation does not support the data of Allen et al, 26 which revealed increased numbers of B cells and expression of BAFF (B-cell-activating factor belonging to the TNF family) in patients with chronic GVHD. This discrepancy may be because the patients with chronic GVHD were on more active immunosuppressants compared with those without chronic GVHD.…”
Section: Discussioncontrasting
confidence: 57%
“…The pathophysiology of chronic GVHD includes defects in thymic function/negative selection (44), Tregs (45), clonal deletion (46)(47)(48), and clonal anergy (49,50). In this study, we showed that the PD-1 pathway contributed to the development of chronic GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, dysregulation of BAFF levels, especially after depletion of cells consuming BAFF, contribute to pathogenic antibody responses, indicating that pan-depletion of B cells can have deleterious effects on disease progression (128)(129)(130)(131). Long-lived plasma cells lack CD20, the target of rituximab, and account for alloantibody production even after mature B cells that express CD20 are depleted.…”
Section: Role In Renal Transplantationmentioning
confidence: 99%